Selection Algorithms of the Optimal Reinforcement for Strength and Crack Resistance of Reinforced Concrete Elements and Their Verification - T. M. Hlukhava (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
One of the main stages in the design of reinforced concrete structures is to determine the crosssectional area of the reinforcement according to the requirements of strength, stiffness and crack resistance, the search for the number of rods based on the nomenclature of reinforcement, its placement in the cross section with the fulfillment of the conditions of durability, and fire resistance. The paper summarizes the experience of developing algorithms for solving the problem of selecting the optimal reinforcement of reinforced concrete elements and proposes an algorithm for optimizing reinforcement using nonlinear models of reinforced concrete elements. The proposed algorithm is implemented as a module of the software package for engineering construction calculations Beta 5.0. The article shows the results of verification of the proposed algorithms based on the results of trial operation of the module for selecting the optimal reinforcement within the activities of the Testing and Research Center of the Polotsk State University.